An Interdisciplinary Weight Loss Program Improves Body Composition and Metabolic Profile in Adolescents With Obesity: Associations With the Dietary Inflammatory Index - Ferreira, Yasmin Alaby Martins; Kravchychyn, Ana Claudia Pelissari; Vicente, Sofia de Castro Ferreira; Campos, Raquel Munhoz da Silveira; Tock, Lian; Oyama, Lila Missae; Boldarine, Valter Tadeu; Masquio, Deborah Cristina Landi; Thivel, David; Shivappa, Nitin; Hébert, James R.; Dâmaso, Ana R. (Frontiers in Nutrition, 2019)
ABSTRACT Background & Aims The prevalence of overweight and obesity consitutes a global epidemic and it is growing around the world. Food and nutrition are essential requirements for promoting health and protecting against non-communicable chronic diseases, such as obesity and cardiovascular disease. Specific dietary components may modulate inflammation and oxidative stress in obese individuals. The Dietary Inflammatory Index (DII®) was developed to characterize the anti- and pro-inflammatory effects of individuals’ diet. Few studies have investigated the role of diet-associated inflammation in adolescents with obesity. The present study aims to investigate the effects of an interdisciplinary weight loss therapy on DII scores and cardiometabolic risk in obese adolescents and possibles correlations. Methods: A total of 45 volunteers (14-19 years old) were recruited and enrolled for long-term interdisciplinary therapy including clinical, nutritional, psychological counseling and exercise training. Adolescents had access to videos about health education weekly. Body composition and inflammatory and serum profiles were evaluated at baseline and after intervention. The food intake was obtained by 24-hour food recall. Data was used to calculate energy-adjusted DII (E-DII) scores. Negative scores indicate an anti-inflammatory diet and positive scores indicates a pro-inflammatory diet. The sample was divided according to whether individuals increased or decreased E-DII scores after therapy. Results: After therapy the body mass index (BMI), body weight, body fat, abdominal, waist, neck and hip circumferences decreased significantly. The mean of high-density lipoprotein cholesterol (HDL-c) increased after the therapy. There was found an improvement of inflammatory and cardiometabolic parameters. In exploratory analyses, this occurred mainly when the EDII improved. Conclusion: Long-term interdisciplinary therapy combined with a health education website improved inflammatory serum markers in obese adolescents. Reduction in DII scores was associated with reduction of cardiometabolic parameters, suggesting that an anti-inflammatory diet may be an effective strategy to prevent and treat obesity and related comorbidities.